Physiology of temperature regulation: Comparative aspects - Bicego, Kenia C.; Barros, Renata C. H.; Branco, Luiz G. S. (Elsevier B.V., 2007)
Few environmental factors have a larger influence on animal energetics than temperature, a fact that makes thermoregulation a very important process for survival. In general, endothermic species, i.e., mammals and birds, maintain a constant body temperature (Tb) in fluctuating environmental temperatures using autonomic and behavioural mechanisms. Most of the knowledge on thermoregulatory physiology has emerged from studies using mammalian species, particularly rats. However, studies with all vertebrate groups are essential for a more complete understanding of the mechanisms involved in the regulation of Tb. Ectothermic vertebrates-fish, amphibians and reptiles-thermoregulate essentially by behavioural mechanisms. With few exceptions, both endotherms and ectotherms develop fever (a regulated increase in Tb) in response to exogenous pyrogens, and regulated hypothermia (anapyrexia) in response to hypoxia. This review focuses on the mechanisms, particularly neuromediators and regions in the central nervous system, involved in thermoregulation in vertebrates, in conditions of euthermia, fever and anapyrexia. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: anapyrexia; ectothermy; endothermy; fever; hypothermia; neural pathways; neuromediators; preoptic area